Pengaruh Pengendalian Internal dan Financial Distress terhadap Konservatisme Akuntansi - Khairani, Kinanti Aurora; Taqwa, Salma (Jurnal Nuansa Karya Akuntansi, 2024)
Financial statements are a description of the company's condition within a certain period of time. One of the principles that can be used to prepare financial statements is the principle of conservatism. The use of accounting conservatism in preparing financial statements can reduce information asymmetry in a company. This study aims to determine how the effect of internal control and financial distress on accounting conservatism. This study used 163 samples of manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2021. The results showed that internal control has no effect on accounting conservatism, while financial distress has a negative effect on accounting conservatism. This research is expected to increase knowledge on the topic of accounting conservatism in manufacturing companies in Indonesia. Suggestions for further research are expected to add other variables that may affect accounting conservatism.